Mosque tourism in the digital age: examining Generation Y's virtual reality experiences - Md Sawari, Siti Salwa; Mat Desa, Sıtı Nuur Hamızah; Hussin, Siti Rahayu; Ab Talib, Mohamed Syazwan (Malaysian Institute of Planners, 2024)
The rise in Muslim travelers and the swift evolution of virtual reality (VR) technology is fundamentally transforming the global tourism industry. This convergence underscores the immediate need for further academic exploration into the potential uses of virtual reality in the domain of Muslim tourism, creating a promising avenue for future research. In this vein, our study aims to evaluate how Generation Y perceives the concept of participating in virtual reality mosque tourism, considering both cognitive and emotional responses from this demographic's perspective. The primary goal of our research is to uncover Generation Y's genuine experiences in virtual reality mosque tourism. Our quantitative research methodology involved 100 Muslim travelers aged between 29 and 41 years. Data analysis was conducted using the IBM Statistical Package for Social Science (SPSS), encompassing both descriptive and Pearson correlation analyses. The findings of our analysis, which indicate that a significant majority of participants found the 360-degree Virtual Reality Mosque Tour enjoyable and captivating, have significant implications for understanding cognitive and emotional responses related to the intention to visit mosques in the tourism context. These findings could potentially shape the future landscape of mosque tourism, making our research a crucial contribution to the field.